Strengthening Public Sector Fraud Prevention Through Internal Control, Good Governance, and Whistleblowing Systems: Evidence from North Sumatra - Henny Zurika Lubis; Debbi Chyntia Ovami; Esa Setiana; Hafsah; Isna Ardila (Academic Bright Collaboration, 2026)
Purpose - This study examines whether internal control, good governance, and whistleblowing systems strengthen fraud prevention at the North Sumatra Provincial Inspectorate. The study responds to the need for an integrated public sector anti-fraud model within a regional government supervisory institution. Methods - This study used a quantitative explanatory design. Primary data were collected through structured questionnaires distributed to 41 internal auditors at the North Sumatra Provincial Inspectorate. The sample was selected using proportionate stratified random sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.0. Findings - The results indicate that internal control has a positive and significant effect on fraud prevention (β = 0.457; t = 3.682; p < 0.001). Similarly, good governance has a positive and significant effect on fraud prevention (β = 0.468; t = 3.720; p < 0.001). In contrast, the whistleblowing system shows a positive but statistically insignificant effect on fraud prevention (β = 0.098; t = 0.900; p = 0.368). Overall, the model explains 86.3% of the variance in fraud prevention. Research implications - The findings indicate that fraud prevention in public sector institutions depends more strongly on effective internal control and accountable governance than on the formal existence of reporting channels alone. Therefore, public institutions should strengthen control procedures, governance practices, whistleblower protection, and follow-up mechanisms. Originality - This study contributes to the fraud prevention literature by integrating internal control, good governance, and whistleblowing systems into one SEM-PLS model in the context of a regional public supervisory institution. It also supports agency theory and contingency theory in explaining how institutional control mechanisms shape fraud prevention.